Acceptance and Commitment Therapy (ACT) to Improve Educators Self-Acceptance of Children with Special Needs - Barida, Muya; Widyastuti, Dian Ari (Universitas Islam Negeri Raden Intan Lampung, 2019)
Children with Special Needs are children with disabilities in the development of life due to disruption (mental, intellectual, emotional, social, physical) in the social-social, career, and academic fields, so they need special services and are different from children in general. This study aims to determine the effectiveness of Acceptance and Commitment Therapy (ACT) to increase the self-acceptance of educators towards Children with Special Needs. This study uses an experimental approach to the design of one group pretest-posttest. The study was conducted on teachers who are members of the HIMPAUDI Sleman District, who were randomly selected and obtained as many as 27 teachers. Data analysis was performed using the T-Test technique. Based on the results of the study, it appears that the self-acceptance of educators towards Children with Special Needs before and after the training on Acceptance and Commitment Therapy (ACT) increases, but the increase is less significant. Conclusion The Acceptance and Commitment Therapy (ACT) program is less effective in improving the self-acceptance of educators towards Children with Special Needs. Based on these results, it needs to be followed up with direct assistance or assistance in schools for educators who systematically help Children with Special Needs.